An Investigation On: Using Literature Circles to Enhance Reading’ Engagement With Literary Texts The Case of Undergraduate ELTStudents at Laghouat University - Miloudi ,Safaa; Nouioua ,Amira Hiba (Faculty of Letters and Foreign Languages Department of English, 2018)
This research aims at investigating on the problems undergraduate students face with literature mainly the problem of engagement. To prove also that teachers ignore that a lot of students do not feel engaged with reading in class. In order to achieve that this research was conducted in the University of Laghouat dealing with teachers of literature, and undergraduate students. The data was gathered through the interview addressed to teachers of literature at the Department of English, and the questionnaires provided to undergraduate students. The results collected from the questionnaires and the interview were analyzed quantitatively. The final result found that not all students are engaged with reading in class. A number of students have answered that they do not feel engaged when there is reading in class. The result found that literature circles is new and not used by teachers of literature. However, students got an idea about the way literature circles work. The majority answered that literature circles engage them with reading, and create a collaboration in class. To conclude the results, this research reached the point that both students and teachers ignore about literature circles. In order to practice literature circles, the teacher needs to make the groups meet regularly. In addition, providing the groups with roles and make students the center of the discussion.